2009
DOI: 10.2220/biomedres.30.189
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic bactericidal action of fluorescent light in a titanium dioxide particle mixture: an in vitro study

Abstract: Traditional titanium dioxide (TiO 2 ) has photocatalytic bactericidal properties only under ultraviolet (UV) irradiation, which restricts its use in clinical treatment regimens. In this study, we evaluated the photocatalytic bactericidal effects of an aqueous system of TiO 2 particles irradiated by fluorescent light (FL) on Staphylococcus aureus. A TiO 2 particle mixture containing 19 ppm (0.019 mg/ mL) of TiO 2 was prepared. A bacterial solution of 1 × 10 5 CFU/mL was added one drop at a time to the TiO 2 mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 16 publications
2
3
0
1
Order By: Relevance
“…Since the method of rapid colorimetric MTT is based on metabolic cell activity, the present study results can be more reliable than those reported by Sawase et al (2008), where counting the number of adherent cells was performed by laser microscopy and specialized software; on the other hand Onuki et al (2010) detached with trypsin adherent cells and cell counting was performed with hemocytometer and finally Koseki et al (2009) isolated cells from the surface with trypsin and ultrasonic waves, those methods previously reported are ineffective for correct estimate of the number of viable cells. However, the MTT method has a limitation, minimum cells still remain on the surface, underestimation due to lack of contact time MTT reagent with cells, therefore, in future research an increase in the incubation time of the reagent with cells is recommended.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Since the method of rapid colorimetric MTT is based on metabolic cell activity, the present study results can be more reliable than those reported by Sawase et al (2008), where counting the number of adherent cells was performed by laser microscopy and specialized software; on the other hand Onuki et al (2010) detached with trypsin adherent cells and cell counting was performed with hemocytometer and finally Koseki et al (2009) isolated cells from the surface with trypsin and ultrasonic waves, those methods previously reported are ineffective for correct estimate of the number of viable cells. However, the MTT method has a limitation, minimum cells still remain on the surface, underestimation due to lack of contact time MTT reagent with cells, therefore, in future research an increase in the incubation time of the reagent with cells is recommended.…”
Section: Discussionsupporting
confidence: 62%
“…The first report of the use of photocatalysis back to 1970 (Fujushima & Honda, 1972) several studies have focused on the antibacterial effects and sterilization with UV irradiation (Xu et al, 2006;Koseki et al, 2009). The present study confirms further that the UV light irradiation on the titanium plates for 20 min improves adhesion and proliferation of fibroblasts and significantly enhances the cell attachment when TiO 2 NPs were present on the Ti plates.…”
Section: Discussionmentioning
confidence: 99%
“…All these ensured that all the photocatalyst containing sites would be activated. Desai and Kaushik synthesized TiO 2 by sol-gel technique and studied its inhibitory photocatalytic activity against some common pathogenic micro organisms such as E. coli, P. aeruginosa, K. pnemoniae, S. aureus under visible illumination [24]. The antimicrobial activity of TiO 2 -PMMA combination is in accordance with the study conducted by Desai and Koseki et al which evaluated the photocatalytic bactericidal effects of TiO 2 on S. aureus when irradiated.…”
Section: Exposure Of Specimens To Lightsupporting
confidence: 68%
“…Böylece negatif yüklü elektron ve pozitif yüklü boşluk çifti meydana gelir ve sonuçta fotokatalizör çok güçlü redüksiyon ve oksidasyon yeteneği kazanır. Su ve oksijen molekülleri, fotokatalizör etkisi ile hidroksil ve süperoksit anyonları meydana getirirler [5][6][7]. Fotokatalizör sistemler, çevre ve insan için zararlı olan molekül-ler üzerindeki parçalayıcı etkisinin yanında, bakteriostatik ve bakterisit etkisini de serbest oksijen radikalleri aracılığı ile yaparlar.…”
Section: Discussionunclassified